Ethical Awareness of AI Overreliance in Academic Writing: A Systematic Literature Review - Siska; Melvina; Lydia, Mariana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The increasing use of Artificial Intelligence (AI) has transformed academic writing by enabling students to generate ideas, improve language quality, and complete writing tasks more efficiently. However, excessive dependence on AI has raised concerns regarding ethical awareness and academic responsibility. This study aims to examine the ethical implications of AI overreliance in academic writing through a systematic literature review. Relevant studies published between 2023 and 2025 were selected and analyzed to identify key issues related to academic integrity, authorship, accountability, transparency, and responsible AI use. The findings indicate that AI overreliance may weaken students’ sense of ownership over their work, reduce critical evaluation of information, and create uncertainty regarding ethical writing practices. Furthermore, limited AI literacy and unclear institutional guidelines contribute to inappropriate AI use. The study concludes that ethical awareness plays a crucial role in ensuring responsible AI-assisted writing. Therefore, higher education institutions should promote ethical AI literacy and establish clear policies to maintain academic integrity.